Co-producing artistic approaches to social cohesion. (22nd September 2020) - Goldstraw, Katy; McMillan, Andrew; Mort, Helen; Pahl, Kate; Pool, Steve; Rafiq, Zahir; Rasool, Zanib
Abstract : page_257 other This paper examines the potential of co-produced arts-based methodologies through the lens of a social cohesion project, from the perspectives of five artists. Arts methodologies can be useful in working across different disciplines and across university and community boundaries to create equitable knowledge production processes. The ways in which art is used in community settings as a mode of collaboration are explored, using the reflections from five artists who were involved in the social cohesion project together. This paper argues that co-producing artistic approaches to social cohesion is a complex, multilayered and sometimes fragile process, but that recognizing and discussing understandings of the role of power and voice within co-produced projects enables effective team communication.